On Jupiter’s Cult from the South of the Roman Province of Dalmatia (A few examples from East Herzegovina) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The statues testifying about the Roman citizens’ religiousness were found in the south of the Roman province of Dalmatia (east Herzegovina) as well as in all areas that were once the parts of the Roman Empire. In alliance between men and Gods, the Roman citizens respected always and everywhere the given cult rituals, presented offerings, and prayed. Therefore, a smaller number of epigraph statues was preserved to testify today about their former existence. The Romans (soldiers, colonists) brought with themselves the respect for the cult of the deity of the Roman state Pantheon, among which, the most respected one was the supreme Roman god, Jupiter. There is a certain number of statues devoted to this deity that were found on the territory of east Herzegovina. Jupiter is most frequently recorded alone on the territory of east Herzegovina while in the surrounding areas, it is recorded in the cult together with Juno and Minerva (the Capitoline Triad) and together with other deities (usually Mars). The most common form of dedication in east Herzegovina is the well-known abbreviation – IOM, but there are other attributes in the surrounding areas such as Victor, Conservator, Depulsor, Dolichenus, Fulminator, etc. The respect for this supreme Roman deity represents one of the main indicators of the influence of romanization which spread thanks to Roman soldiers and other dignitaries from the Empire’s administration. This was proved by the epigraph inscription dedicated to Jupiter and found in Oklada, Stolac. It can be seen from the inscription that Jupiter’s cult could have existed within the beneficiary’s station in which dignitaries dedicated themselves while accepting their annual duties. The Roman soldiers and representatives of the Empire’s administration were recorded as the representatives of the Jupiter’s cult in east Herzegovina. This fact leads to a conclusion that this area was under the direct influence of the Roman Empire.